Prognostic Nutritional Index in Hepatocellular Carcinoma Patients With Hepatitis B Following US-Guided Percutaneous Microwave Ablation: A Retrospective Study With 1,047 Patients - 萍, 梁; 雅晳, 王; 鑫, 李; 志刚, 程; 杰, 于; 启迪, 侯 (Frontiers in Surgery, 2022)
Abstract Objective: Several studies have revealed that prognostic nutritional index (PNI) was associated with survival in several cancers. However, the prognostic value of PNI in hepatocellular carcinoma (HCC) patients followed ultrasound-guided percutaneous microwave ablation (US-PMWA) remains unknown, especially in patients with hepatitis B virus (HBV) infection. So, the present study aimed to evaluate the potential prognostic value of PNI in these patients. Materials: The medical records of 1047 HCC patients with HBV infection followed US-PMWA were retrospectively reviewed. The association between preoperative PNI and overall survival (OS), as well as clinical characteristics of HCC, were analyzed using the Kaplan-Meier plot, log-rank test, multi-parameter Cox proportional hazards model, restricted cubic spline (RCS) and time-dependent receiver operating characteristic (ROC) curves analysis